An investigation into the uniformity and non-uniformity of online/offline retail brand building in South Africa - H. Kruger; L. C.H. Fourie (South African Journal of Business Management, 2003)
Brand equity or -value is the result of the design and implementation of brand building, – measurement and – management programs. Brand building focuses on three interdependent tiers: selecting brand elements, choosing certain marketing activities and programs, and linking the brand to secondary brand associations. A brand holder's first instinct may be, when it decides to evolve to the Internet, to maintain the status quo of its offline brand equity or value, by building a uniform online/offline brand. However, from the literature it is evident that authors are not united in their support of building uniform online/offline brands. Although building a uniform online/offline brand present certain tangible advantages, uniformity or non-uniformity proves not to be a binary decision, but dependant on the strategic imperative of the three tiered online/offline brand building initiative. To research three tiered online/offline brand building from a South African perspective, the uniformity and non-uniformity of brand name selection within the South African online/offline retail environment is firstly investigated. The advantages of building uniform online/offline brands are secondly elucidated as presented by the marketing programs – and activities of selected South African retail brands. Secondary brand associations, as part of the three tiered brand building phase or as separate strategic imperative, and the role it plays in non-uniform online/offline brand building, is thirdly examined. Findings are summarised, conclusions are drawn that elucidate the uniform and non-uniform brand building strategies of South African online/offline retailers and recommendations are made for future research.
Keywords: 650